The Effects of One versus Two Years of Intensive Reading Intervention Implemented with Late Elementary Struggling Readers - Miciak, Jeremy (Learn Disabil Res Pract, 2017)
We examined the effectiveness of a researcher-provided reading intervention with 484 fourth graders with significant reading difficulties. Students were randomly assigned to one year of intervention, two years of intervention, or a business-as-usual comparison condition (BAU). Students assigned to two years of intervention demonstrated significantly greater gains in reading fluency compared to students who received one year of intervention and the BAU group. Students in both the one- and two-year groups demonstrated similar and significantly larger gains in word reading in comparison to the BAU group. There were no statistically significant differences between the three groups on standardized measures of reading comprehension. We discuss these results in the context of research with late elementary and secondary students targeting reading comprehension.